2001
DOI: 10.1007/s004360100382
|View full text |Cite
|
Sign up to set email alerts
|

Viability and infectivity of oocysts recovered from clams, Ruditapes philippinarum , experimentally contaminated with Cryptosporidium parvum

Abstract: This study confirms the important role of marine bivalve molluscs, destined for human consumption, as transmitters of cryptosporidiosis, zoonotic diarrhoeal disease caused by Cryptosporidium parvum. C. parvum oocysts recovered from seawater clams (Ruditapes philippinarum) were viable and infective in five of eight infected neonatal CD-1 Swiss mice. Oocysts were observed in clam gill and gastrointestinal tract tissue homogenates as well as in gill histological sections, by an immunofluorescent antibody techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Experiments conducted in aquaria indicate that T. gondii and C. parvum oocysts can be retained in the bivalve for long periods in the gastrointestinal tract, gills, hemolymph, and intervalvular liquid [38,39,40,41,42,43,44]. It has been reported that C. parvum recovered from environmental samples retain viability [45], and although salinity affects the viability of C. parvum oocyst, they remain active for up to four weeks in estuarine conditions [33]. An approximation of the parasite load of wild mussels collected in C. parvum positive sites indicated that each shellfish transports between 6 and 1000 oocysts [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments conducted in aquaria indicate that T. gondii and C. parvum oocysts can be retained in the bivalve for long periods in the gastrointestinal tract, gills, hemolymph, and intervalvular liquid [38,39,40,41,42,43,44]. It has been reported that C. parvum recovered from environmental samples retain viability [45], and although salinity affects the viability of C. parvum oocyst, they remain active for up to four weeks in estuarine conditions [33]. An approximation of the parasite load of wild mussels collected in C. parvum positive sites indicated that each shellfish transports between 6 and 1000 oocysts [46,47].…”
Section: Discussionmentioning
confidence: 99%